Pengaruh Thin Capitalization Dan Capital Intensity Terhadap Penghindaran Pajak - Prananda, Windi; Tumirin, Tumirin (Universitas 17 Agustus 1945 Jakarta, 2025)
This study aims to analyze the influence of thin capitalization and capital intensity on tax avoidance. It focuses on multinational companies within the manufacturing sector that are listed on the Indonesia Stock Exchange (IDX) over a period of six years, specifically from 2018 to 2023. The research employs a nonprobability sampling method, utilizing purposive sampling techniques to select from the existing population of firms. The data utilized in this study consists of secondary data sourced from the financial statements of the companies involved. Additionally, the study is grounded in the Theory of Planned Behavior (TPB), which serves as a theoretical framework to elucidate managerial behavior regarding tax avoidance practices. The findings reveal that thin capitalization has a significant impact on tax avoidance, indicating that companies with lower capital ratios are more likely to engage in tax avoidance strategies. In contrast, capital intensity does not demonstrate a significant effect on tax avoidance, suggesting that the level of capital investment does not play a crucial role in these practices among the companies analyzed